PENGARUH TINGKAT PENDIDIKAN DAN DISIPLIN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI - ANDI HASRYNINGSIH ASFAR; SARIPUDIN SAPUTRA (AKADEMIKA, 2018)
The purpose of this research is know whether there is influence between education level (X1), to work effectiveness (Y), how much influence between the education level (X1), to work effectiveness (Y),is there influence between work discipline (X2), to work effectivess (Y), how much influence between the wok discipline tto work effectiveness (Y), to find out wheter the education level (X1),and work discipline(Y), together affect the effectiveness of work (Y), to know which variable gives dominant influence to work effectiveness(Y). The method used in this research is survey method, with correlation and regression quantiative approach. The sample size is 64 people taken from employees Dinas Kependudukan dan Pencatatan Sipil Kabupaten Serang. The method of data processing using multiple regression analysis.The results showed that the variable level of education (X1) has a positive significant effect on the effectiveness of work (Y) as evidenced by the coeffient of education level variable with actual test t values 8.642 >1.999, α = 0.05, the work disciplines has a t stat of 10,769, whose values is greater than ttable (1.999, α = 0.05). This mean work diciplines has a positive and significant effect on effecstiveness of work based on F test shows that the regression has F-stat values of regression has F-stat equal to 61,697, thevalues is greater than the F-table of 3.15 at a 95% confidence level, so it can be concluded that together, independent variables effect the dependent variable.Conclusion of research based on the above calculation then there is a significant influence between the level education on the effectiveness of employees and there is a significant influence between work diciplines on the effectiveness of employee work. Based on the analysis results can be concluded that simultaneously independent variables level of education and work discipline significantly influence the effectiveness of employees in Dinas Kependudukan dan Pencatatan Sipil Kabupaten Serang